Olaparib combined with abiraterone in patients with metastatic castration-resistant prostate cancer: a randomised, double-blind, placebo-controlled, phase 2 trial. Issue 7 (July 2018) - Clarke, Noel; Wiechno, Pawel; Alekseev, Boris; Sala, Nuria; Jones, Robert; Kocak, Ivo; Chiuri, Vincenzo Emanuele; Jassem, Jacek; Fléchon, Aude; Redfern, Charles; Goessl, Carsten; Burgents, Joseph; et al.
Summary: Background: Patients with metastatic castration-resistant prostate cancer and homologous recombination repair (HRR) mutations have a better response to treatment with the poly(ADP-ribose) polymerase inhibitor olaparib than patients without HRR mutations. Preclinical data suggest synergy between olaparib and androgen pathway inhibitors. We aimed to assess the efficacy of olaparib plus the androgen pathway inhibitor abiraterone in patients with metastatic castration-resistant prostate cancer regardless of HRR mutation status. Methods: We carried out this double-blind, randomised, placebo-controlled phase 2 trial at 41 urological oncology sites in 11 countries across Europe and North America. Eligible male patients were aged 18 years or older with metastatic castration-resistant prostate cancer who had previously received docetaxel and were candidates for abiraterone treatment. Patients were excluded if they had received more than two previous lines of chemotherapy, or had previous exposure to second-generation antihormonal drugs. Patients were randomly assigned (1:1) using an interactive voice or web response system, without stratification, to receive oral olaparib 300 mg twice daily or placebo. All patients received oral abiraterone 1000 mg once daily and prednisone or prednisolone 5 mg twice daily. Patients and investigators were masked to treatment allocation. The primary endpoint was investigator-assessed radiographic progression-free survival (rPFS; based on Response Evaluation Criteria in Solid Tumors version 1.1 and Prostate Cancer Clinical Trials Working Group 2 criteria). Efficacy analyses were done in the intention-to-treat population, which included all randomly assigned patients, and safety analyses included all patients who received at least one dose of olaparib or placebo. This trial is registered withClinicalTrials.gov, numberNCT01972217, and is no longer recruiting patients. Findings: Between Nov 25, 2014, and July 14, 2015, 171 patients were assessed for eligibility. Of those, 142 patients were randomly assigned to receive olaparib and abiraterone (n=71) or placebo and abiraterone (n=71). The clinical cutoff date for the final analysis was Sept 22, 2017. Median rPFS was 13·8 months (95% CI 10·8–20·4) with olaparib and abiraterone and 8·2 months (5·5–9·7) with placebo and abiraterone (hazard ratio [HR] 0·65, 95% CI 0·44–0·97, p=0·034). The most common grade 1–2 adverse events were nausea (26 [37%] patients in the olaparib group vs 13 [18%] patients in the placebo group), constipation (18 [25%] vs eight [11%]), and back pain (17 [24%] vs 13 [18%]). 38 (54%) of 71 patients in the olaparib and abiraterone group and 20 (28%) of 71 patients in the placebo and abiraterone group had grade 3 or worse adverse events, including anaemia (in 15 [21%] of 71 patients vs none of 71), pneumonia (four [6%] vs three [4%]), and myocardial infarction (four [6%] vs none). Serious adverse events were reported by 24 (34%) of 71 patients receiving olaparib and abiraterone (seven of which were related to treatment) and 13 (18%) of 71 patients receiving placebo and abiraterone (one of which was related to treatment). One treatment-related death (pneumonitis) occurred in the olaparib and abiraterone group. Interpretation: Olaparib in combination with abiraterone provided clinical efficacy benefit for patients with metastatic castration-resistant prostate cancer compared with abiraterone alone. More serious adverse events were observed in patients who received olaparib and abiraterone than abiraterone alone. Our data suggest that the combination of olaparib and abiraterone might provide an additional clinical benefit to a broad population of patients with metastatic castration-resistant prostate cancer. Funding: AstraZeneca.